Hoaks Sebagai Tindak Pidana Pemilihan Umum: Hoax as Election Criminal Offences - Vidya Prahassacitta (Asosiasi Pengajar Hukum Pidana dan Kriminologi Indonesia (ASPERHUPIKI), 2024)
The purpose of the research is to analyze hoaxes during elections as special crime offenses. This research is documentary research using a statistical approach. The research shows that fabrication and distribution hoaxes about elections are part of the black campaign. There is difficulty in addressing hoax as an election criminal offense. First, to deter the clear and present danger of a hoax if it does not follow with direct harm to society. Second, formulation as delicta propria: offenses that are only committed by people who have certain qualifications and require certain time to commit criminal offenses during the campaign period only.